DETERMINING THE PERCEPTION OF EASE OF USE, PERCEPTION OF BENEFITS AND TRUST IN PURCHASING DECISIONS IN SHOPEE E-COMMERCE ACCORDING TO ISLAMIC BUSINESS PERSPECTIVE (Study On Generation Z Of Shopee Users In Bandar Lampung) - Wardiansyah; Habibi, Ahmad; Susanti, Yeni (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
In Indonesia Shopee is one of the largest E-commerce platforms that makes it easy for users to access various products from various brands. Factors such as perceived ease of use, perceived benefits, and trust attached to shopee become a positive image and improve purchasing decisions in shopee e-commerce. These factors, it is expected to find an effective strategy according to Islamic Business Principles, which is not only economically beneficial but also provides broader social benefits. this study is to determine the perception of ease of Use, perception of benefits, and confidence in purchasing decisions, as well as how the view of Islamic Business. The paradigm of this study using positivistic (quantitative) with a descriptive approach. The test Data is primary data. The population used in this study is Gen Z Shopee application users in Bandar Lampung City with a total sample of 100 respondents with SmartPLS Analysis tool version 4. The results show that the perception of user convenience, perception of benefits and Trust have a significant positive effect on Shopee's e-commerce purchasing decisions. Islamic business principles not only improve service efficiency and customer satisfaction but also ensure that business operations remain ethical and in accordance with Islamic teachings this will build long-term trust between the company and customers which is the core of sustainable business success.